Análisis polínico de mieles de la zona noroccidental de Marruecos: región de Targuist - Terrab, Anass; Valdés, Benito; Díez, María J. (Lazaroa, 2001)
Sixteen honey samples directly provided by amateur beekeepers from Targuist were analysed. A total of 43 pollinic types belonging to 28 families were identified using microscopic analysis. Results show that nectar is the main source of honey in the study area and that two sample belong to Maurizio’s Class V, four to Class IV, two to Class III and one to Class II. Two of the honey samples were unifloral Mentha species.